2004
DOI: 10.1017/s0008423904030094
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion and Policy Making in Canada 1994–2001

Abstract: Abstract. This study examines the consistency between public opinion and public policy during the period 1994–2001 by matching responses to national survey questions on 230 issues with enacted policy proposals on the same issues. Policy outcomes were consistent with majority opinion 49 per cent of the time. This represents a significant drop from 69 per cent during the Mulroney years (1985–1993). Low opinion-policy consistency since 1994 is primarily attributable to divergences between public majorities tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…En relación con las políticas tratadas, la literatura proporciona un claro mensaje general: la visibilidad del tema será crucial para que las encuestas sean más o menos habituales (Barreiro, 1998;Burstein, 2006), puesto que los datos sobre opinión pública serán más creí-bles en relación con temas más visibles y conocidos (Druckman y Jacobs, 2006) y porque la responsiveness solo tendrá consecuencias electorales en los temas muy destacados (Petry y Mendelson, 2004). En consecuencia, los gobiernos tendrán muchos más incentivos para encuestar sobre temas políti-camente relevantes que sobre otros donde pueden elegir más libremente el tomar sus rutas favoritas (10).…”
Section: Los Objetivos De Las Encuestas: Para Quéunclassified
“…En relación con las políticas tratadas, la literatura proporciona un claro mensaje general: la visibilidad del tema será crucial para que las encuestas sean más o menos habituales (Barreiro, 1998;Burstein, 2006), puesto que los datos sobre opinión pública serán más creí-bles en relación con temas más visibles y conocidos (Druckman y Jacobs, 2006) y porque la responsiveness solo tendrá consecuencias electorales en los temas muy destacados (Petry y Mendelson, 2004). En consecuencia, los gobiernos tendrán muchos más incentivos para encuestar sobre temas políti-camente relevantes que sobre otros donde pueden elegir más libremente el tomar sus rutas favoritas (10).…”
Section: Los Objetivos De Las Encuestas: Para Quéunclassified
“…2. For consideration of the linkage between public opinion and policy outcomes, see Petry and Mendelsohn (2004) and Soroka and Wlezien (2004). 3.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…In addition, there exists a rich literature on the mediating role of public issue salience in democratic politics, which explores other aspects of the relationship between public opinion and 926 K. Oppermann and H. Viehrig policy-making. For one thing, numerous studies have shown that policy outcomes are more consistent with public preferences in cases of high issue salience than in cases of low issue salience (Page and Shapiro 1983;Monroe 1998;Petry and Mendelsohn 2004). Such consistency, moreover, is more likely to result from a bottom-up rather than a top-down process when the salience of the issue in question is high (Hill and Hurley 1999).…”
Section: The Concept Of Public Saliencementioning
confidence: 99%